Ferdinand's Bridge in Vienna - Unknown:::Creator::::::::::::; Meyer, Joseph, 1796-1856 (author):::Contributor:::::::::::: (Hildburghausen; Kunstanst d. Bibliographisches Institut; Germany)
Steel engraving with a view of the Ferdinandsbrücke in Vienna, with people in the foreground and crossing the bridge.